2017
DOI: 10.1021/acscatal.7b00513
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Cascades in Whole Cells for the Synthesis of Chiral Cyclic Amines

Abstract: The increasing diversity of reactions mediated by biocatalysts has led to development of multi-step in vitro enzyme cascades, taking advantage of generally compatible reaction conditions. The construction of pathways within single whole cell systems is much less explored, yet has many advantages. Herein we report the generation of a successful whole cell de novo enzyme cascade for the diastereoselective and/or enantioselective conversion of simple, linear keto acids into valuable cyclic amine products. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 44 publications
0
65
0
Order By: Relevance
“…[12] In conclusion, we have shown that in the absence of NADPH, the adenylation activity of CARs can be exploited for amide bond formation. These variants might have application as amidation catalysts in more complex enzyme cascades,b oth in cell-free and whole-cell systems,w here the presence of NADPH would normally suppress CAR-mediated amidation in favor of reduction.…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…[12] In conclusion, we have shown that in the absence of NADPH, the adenylation activity of CARs can be exploited for amide bond formation. These variants might have application as amidation catalysts in more complex enzyme cascades,b oth in cell-free and whole-cell systems,w here the presence of NADPH would normally suppress CAR-mediated amidation in favor of reduction.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Thea denylation domain activates carboxylic acids by catalyzing the formation of an acyl adenylate intermediate,a tt he expense of adenosine triphosphate (ATP). [11][12][13] nicotinamide adenine dinucleotide phosphate (NADPH) is then expended to reduce the intermediate to an aldehyde ( Figure 1).…”
mentioning
confidence: 99%
“… Cascade biotransformations of ketones with E. coli cells. a) Conversion of α‐chloroketones to ( R )‐ or ( S )‐β‐hydroxynitriles; b) conversion of δ‐keto acids to substituted chiral piperidines; c) conversion of α,β‐unsaturated ketones to chiral epoxy ketones or epoxy alcohols …”
Section: Recent Development Of Whole‐cell Cascade Biotransformationsmentioning
confidence: 99%
“…Recently, Flitsch et al. developed a single whole‐cell version of the above cascade (Scheme b) . Two different ω‐TAs (ATA‐117, SitATA), two different CARs (NCAR, MCAR), two different IREDs (R‐IRED, S‐IRED), and one 4′‐phosphopantetheinyl transferase (Sfp, to activate CAR) were combinatorially engineered to give eight strains, each containing one combination of the four enzymes.…”
Section: Recent Development Of Whole‐cell Cascade Biotransformationsmentioning
confidence: 99%
“…The addition of a duplicate ( S )‐IRED gene into an original construct significantly improved the conversion of amines, circumvented the accumulation of imine intermediate and drove the reaction toward amine production. The use of a single whole‐cell system provided access to piperidines with high conversion (up to 93 %) and enantiomeric excess (up to 93 %) …”
Section: Artificial In Vivo Cascadesmentioning
confidence: 99%